PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR GAMBAR TEKNIK MATERI - RIZAL WILSANDRA PURBA (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
This research is done in SMKN 3 Sorong about application problem based learning Of Engineering Drawings With Orthogonal Pictoral Projection For X Garde Techanical Engineering in SMKN 3  Sorong for school year 2020/2021. The aim this research to know is the influence of application problem based learning models in inproving the result of learning to the students in the subject Of Engineering Drawings With Orthogonal Pictoral Projection in SMKN 3 Sorong. The type of this research is classroom action research which is implemented in three cycles, which one cycle consists of four components, they are planning, action, observation, and reflection. Technique of data collection is use observation and test. Analysis of data it done in three stages, namely reduction presentation and draw a conclusion. Result of this research show that utilization problem based learning models can increase the result of learning students in the subject Of Engineering Drawings With Orthogonal Pictoral Projection can be seen through aspect of knowledge in first cycles by 70% increased to 95% in second cycles, and can be maintained the result of learning student in third cycles by 95%. While the result of learning to the students in aspect of skills in firsth cycle by 86,6% increased to 90,45% in second cycles, and in third cycle increased too by 91,5%.